Akhlakul-Karimah Siswa Ma’had Islamy: Ditinjau dari Kemampuan Berpikir Kritis - Eva Latipah; Mardliyah, Nur Faizatul (Yogyakarta: Jurusan Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2020)
The akhlakul karimah is the main goal of Islamic education. Psychological factor that contribute to akhlakul-karimah is critical thinking. This study aims to examine the correlationbetween and contribute of critical thinking and akhlakul-karimah. This research is a quantitative approach, using two scales in data gathering. The subjects are 61 students, class of VIII MTs Ma`had Islamy Banguntapan Bantul. Analysis techniques using descriptive analysis and product moment. The results shows: 1) Akhlakul-karimah of students are in the good category, it seem from mean score (of 83.21). 2) Critical thinking of students are in the quite good category, it seem from mean score (57.87). 3) There is a significant and positive correlation between the critical thinking and akhlakul-karimah of students, it seem from r=0.331 and p=0.009 (p <0.05). Critical thinking contributed to akhlakul karimah is 10.9%; the rest (89.1%) is influenced by other variables.